2007
DOI: 10.1089/vbz.2007.0216
|View full text |Cite
|
Sign up to set email alerts
|

Mortality And Reproductive Dynamics of Aedes aegypti (Diptera: Culicidae) Fed Human Blood

Abstract: Mortality is a critical factor in determining a mosquito's ability to transmit pathogens. We investigated the effect of human blood feeding and reproduction on mortality of the dengue virus vector, Aedes aegypti, by conducting a life-table study of male and female mosquitoes maintained on one of three diets: 10% sucrose, human blood or human blood plus 10% sucrose. We examined the effect of host availability by offering human blood to mosquitoes every day or every other day. Mortality of females was age-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 29 publications
3
73
2
Order By: Relevance
“…A growing number of studies have shown age-dependent mortality in mosquitoes, [28][29][30][31][32] but the form of the relationship between age and mortality and how it changes in space and time in natural systems are not known for most mosquito vector species. Accurate estimates of age-dependent mortality are important, because adult survival determines the probability that a mosquito will live long enough to become infectious and transmit a pathogen during its lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have shown age-dependent mortality in mosquitoes, [28][29][30][31][32] but the form of the relationship between age and mortality and how it changes in space and time in natural systems are not known for most mosquito vector species. Accurate estimates of age-dependent mortality are important, because adult survival determines the probability that a mosquito will live long enough to become infectious and transmit a pathogen during its lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest temperature at which yellow fever infectiousness has been observed to develop in a mosquito is approximately 16.5°C. 21 Although the model predicts that it may occur at lower temperatures, the estimated life span of a mosquito is 30-50 days under ideal conditions, 47 and it is shorter at lower temperatures, 48 making it unlikely for a mosquito to survive a complete incubation period. At higher temperatures, in contrast, the probability of a mosquito surviving the much shorter incubation period is correspondingly greater.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the adult life-stage death rates vary by age group. The rate of production of viable eggs per adult is given by b [39].…”
Section: Mathematical Modelmentioning
confidence: 99%